The Influence of Brand Image, Price Perception, and Electronic Word of Mouth (E-WOM) on Purchase Decision in the Gofood Application (A Study of Generation Z in Denpasar City) - A.A. Istri Krisna Gangga Dewi; I Gusti Ayu Nadya Purnamagita; Ni Putu Ayu Tika Kurniawati (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the influence of brand image, price perception, and electronic word of mouth on purchase decisions in the GoFood application among Generation Z in Denpasar City. The research addresses a key issue: a decline in Gross Merchant Value (GMV) on GoFood, alongside a trend of Generation Z shifting to competing platforms such as ShopeeFood. Utilizing a quantitative approach, data were collected from 97 respondents determined using the Cochran formula. The data were analyzed through questionnaires, multiple linear regression, and hypothesis testing. The findings reveal that (1) brand image, price perception, and electronic word of mouth collectively have a positive and significant effect on purchase decisions in the GoFood application among Generation Z in Denpasar City; (2) brand image has a positive and significant individual effect; (3) price perception has a positive but not significant effect; and (4) electronic word of mouth has a positive and significant effect on purchase decisions.